O marco regulatório do lobby no brasil: uma análise comparada dos projetos de regulamentação no congresso nacional de 1984 a 2022 e o caminho para a intermediação democrática de interesses - Bruxellas, Luíza Lucas (2022)
This paper has focused on the normative regulation of lobbying under the purview of the Brazilian legislative process. Through theoretical analysis in the specialized doctrine and literature, it sought to identify the orientational pillars both in favor and against the regulation of the activity. Founded upon those rhetorics, the objective of this paper is to meditate on the impelling purposes of the regulatory activity in a democratic context. On a second step, this reflection has sought to verify the recommended and adopted mechanisms, in distinct engagements and circumstances, on behalf of a successful regulation of lobbying. The verification of the elementary mechanisms for the regulation derived, firstly, from the analytical study of previous efforts by three distinct institutions: the first one being the (i) Organization for Economic Cooperation and Development (OECD); the second being (ii) Transparency International Brazil; and finally reaching the theoretical application elaborated by (iii) The Center for Public Integrity (CPI). Building upon the knowledge and patterns recognized in the verification of regulatory mechanisms, the analysis focused, on a posterior moment, in the examination of the regulations in practice in three different countries, with diversified regulatory orientations. More specifically, the United States of America, which, as we will see further on, has implemented Lobby in a highly regulated manner; Canada, which adopted an intermediate level regulation; and, finally, Germany, which opted for a minimally regulated model. Subsequently, after having reflected critically on the notions and elucidations reached throughout this study, we sought to answer whether the bills proposed by the Brazilian Congress thus far, for the regulation of lobbying activity, have managed to meet the minimum efficacy threshold established by the doctrine for the regulation of the activity